Perbaikan Antarmuka Pengguna pada Aplikasi Malang Menyapa menggunakan Metode Heuristic Evaluation - Lasma Triani; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Department of Culture and Tourism (DISBUDPAR) of Malang City has developed a city tourism application based on the Android system, called Malang Menyapa. Malang Menyapa aims to provide a means to market the cultural and tourism potential of Malang City Based on interview results from staff members of DISBUDPAR of Malang City, there were a few complaints from users regarding the usability aspect, which was satisfaction. An evaluation was required on the usability aspect of the Malang Menyapa application to ease the user in using the user interface, therefore preventing the user from uninstalling the Malang Menyapa application and the main goal of the development of the Malang Menyapa application can be achieved. One of the few methods that can be used to evaluate usability is Heuristic evaluation. Heuristic evaluations involves experts as evaluators to assess whether a design does not comply with the 9 usability principles which were proposed by Monroy. Each problem discovered were giving a severity score rating from a scale of 1-5. The Heuristic evaluation was conducted into two phases. The Evaluators who participated in this research were evaluators who have an understanding of usability. Thirty-nine usability problems were discovered in the first phase of the evaluation. The improvements which were done consisted of 2 phases, which were wireframe designing and hi-fi prototype. The second phase of the evaluation was conducted on the issues discovered in the first phase, the amount of discovered problems in the second phase decreased to 4 usability issues.